Feature Story: Business graduate joins board of Conexus Credit Union - External Relations, University of Regina (External Relations, University of Regina, 2016)
A University of Regina business graduate is one of the newest members of the board of directors of Conexus Credit Union. Bradyn Parisian earned his Bachelor of Business Administration in 2008 at the University of Regina and then returned to the U of R to complete his Masters of Business Administration in 2012. Staff no